Evaluating the comorbidities of age and cigarette smoking on stroke outcomes in the context of anti-complement mitigation strategies - Couch, Christine; Alawieh, Ali M.; Toutonji, Amer; Atkinson, Carl; Tomlinson, Stephen (Frontiers in Immunology, 2023)
Multiple neuroprotective agents have shown beneficial effects in rodent models of stroke, but they have failed to translate in the clinic. In this perspective, we consider that a likely explanation for this failure, at least in part, is that there has been inadequate assessment of functional outcomes in preclinical stroke models, as well the use of young healthy animals that are not representative of clinical cohorts. Although the impact of older age and cigarette smoking comorbidities on stroke outcomes is well documented clinically, the impact of these (and other) stroke comorbidities on the neuroinflammatory response after stroke, as well as the response to neuroprotective agents, remains largely unexplored. We have shown that a complement inhibitor (B4Crry), that targets specifically to the ischemic penumbra and inhibits complement activation, reduces neuroinflammation and improves outcomes following murine ischemic stroke. For this perspective, we discuss the impact of age and smoking comorbidities on outcomes after stroke, and we experimentally assess whether increased complement activation contributes to worsened acute outcomes with these comorbidities. We found that the pro-inflammatory effects of aging and smoking contribute to worse stroke outcomes, and these effects are mitigated by complement inhibition.